Efficient and simple lithium carbonate solution crystallization assembly and method

The lithium carbonate solution crystallization component addresses small crystal volumes and complex processes by employing a freezing, filtering, and crystallization unit with fiber filaments, achieving larger crystals and enhanced efficiency.

CN119113560AActive Publication Date: 2024-12-13SICHUAN AGRI UNIV +1

Patent Information

Application Number
CN202411038020.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2024-12-13
Estimated Expiration
2044-07-31

AI Technical Summary

Technical Problem

Conventional lithium carbonate crystallization methods produce small crystal volumes and involve complex processes, which are inefficient for laboratory-scale preparations.

Method used

A lithium carbonate solution crystallization component comprising a freezing unit, filtering unit, crystallization unit, and drainage unit, utilizing fibers for crystallization treatment, and connected through a peristaltic pump, with specific components like a freezing box, glass rod, filter paper, funnel, crystallizer, and fiber filaments, to enhance crystal growth and efficiency.

Benefits of technology

The method allows for the production of larger lithium carbonate crystals with improved efficiency by freezing, filtering, and crystallizing the solution using fiber filaments, resulting in increased crystal volume and simplified process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119113560A_ABST
    Figure CN119113560A_ABST
Patent Text Reader

Abstract

The invention discloses an efficient and simple lithium carbonate solution crystallization assembly and method. The efficient and simple lithium carbonate solution crystallization assembly at least comprises but is not limited to a freezing assembly, a filtering assembly, a crystallization assembly and a liquid discharging assembly. The freezing unit is used for freezing a prepared solution, the filtering assembly is used for filtering the frozen solution, the crystallizing assembly is used for crystallizing the filtered solution, and the liquid discharging assembly is used for discharging waste liquid in the crystallizing assembly; fibers are arranged in the crystallization assembly for crystallization treatment, and the filtering assembly and the liquid discharging assembly are connected with the crystallization assembly through a pump body; compared with a traditional crystallization mode, crystallization is carried out in a fiber mode, and crystals with larger particles can be condensed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of lithium carbonate solution crystallization, and in particular to an efficient and simple lithium carbonate solution crystallization component and method. Background Art

[0002] Lithium carbonate is widely used. As the core raw material of the lithium battery industry, its main use at this stage is to prepare lithium battery positive electrode materials for use in new energy vehicles and energy storage. The terminal consumption of lithium carbonate is mainly the application of industrial-grade lithium carbonate and battery-grade lithium carbonate. Battery-grade lithium carbonate is ultimately used in electronic consumption in downstream industries, and new energy batteries are the main application direction; while industrial-grade lithium carbonate can be used in lubricants, catalysts, traditional ceramics, glass and other industries, and can also be purified to obtain battery-grade lithium carbonate for application in new energy industries.

[0003] The raw material of the crystalline lithium carbonate prepared in the laboratory is lithium carbonate powder with a high concentration, and then the powder is subjected to a crystallization experiment; the crystal volume obtained by the conventional crystallization method in the prior art is relatively small and cannot meet the requirements of the prior art. Summary of the invention

[0004] The purpose of the present invention is to provide an efficient and simple lithium carbonate solution crystallization component and method to address the above-mentioned shortcomings, thereby solving the problems of small crystal volume and complex crystallization process when preparing lithium carbonate crystals in the laboratory in the prior art.

[0005] The present invention is achieved through the following scheme:

[0006] An efficient and simple lithium carbonate solution crystallization component, at least including but not limited to a freezing component, a filtering component, a crystallization component and a drainage component; the freezing unit is used to freeze the configured solution, the filtering component is used to filter the frozen solution, the crystallization component is used to crystallize the filtered solution, and the drainage component is used to discharge waste liquid in the crystallization component; the crystallization component is provided with fibers for crystallization treatment, and the filtering component and the drainage component are connected to the crystallization component through a pump body.

[0007] Based on the structure of the above-mentioned efficient and simple lithium carbonate solution crystallization component, the freezing component is a freezing box, and the filtering component is a glass rod, filter paper and a funnel; the filter paper is put on the funnel, and the lithium carbonate solution is drained onto the filter paper through the glass rod for filtration; the filtering component and the drainage component are respectively connected to the crystallization component through a peristaltic pump.

[0008] Based on the structure of the above-mentioned efficient and simple lithium carbonate solution crystallization component, the crystallization component includes a crystallizer, a cover body, a glass carrier and fiber filaments; the fiber filaments are arranged on the glass carrier, the upper end of the crystallizer is opened, the cover body is covered on the crystallizer, and the cover body is provided with air holes.

[0009] Based on the structure of the above-mentioned efficient and simple lithium carbonate solution crystallization component, the crystallization component includes a crystallizer, a cover, a crystallization frame, tree-shaped side-by-side fine glass pieces and fiber filaments; the upper end of the crystallizer is opened, the cover is provided with air holes, the cover is covered on the crystallizer, a plurality of tree-shaped side-by-side fine glass pieces are arranged on the crystallization frame, and the fiber filaments are arranged on the tree-shaped side-by-side fine glass pieces.

[0010] Based on the above-mentioned structure of an efficient and simple lithium carbonate solution crystallization component, the tree-like side-by-side thin glass parts include a main rod portion and supporting thin rods, the supporting thin rods converge at the main rod portion, the bottom of the supporting thin rods forms a support, and the fiber filaments are attached along the length direction of each supporting thin rod and converge at the main rod portion.

[0011] Based on the above-mentioned structure of an efficient and simple lithium carbonate solution crystallization component, the crystallization frame includes a main frame, a support tube and a holding piece; the support tube is arranged at the top position of the main frame, and the holding piece is arranged on the side wall of the support tube away from the main frame, and a rubber pad is arranged on the inner contact part of the holding piece and the support tube.

[0012] Based on the structure of the above-mentioned efficient and simple lithium carbonate solution crystallization component, the air hole is a strip hole, the length of the strip hole is not less than the length of the holding piece, so that the holding piece can pass through the air hole, and the width of the strip hole is not less than the size of the support tube.

[0013] The present invention also discloses an efficient and simple method for crystallizing a lithium carbonate solution; the method specifically comprises the following steps:

[0014] Step 1: subjecting lithium carbonate powder to a solution preparation unit to obtain a saturated lithium carbonate solution;

[0015] Step 2: sending the saturated lithium carbonate solution to a freezing unit to obtain a saturated lithium carbonate solution in the form of an ice-water mixture;

[0016] Step 3: sending the saturated lithium carbonate solution in the form of an ice-water mixture into a filtration unit to remove excess undissolved lithium carbonate powder to obtain a pretreated saturated lithium carbonate solution;

[0017] Step 4: The pretreated lithium carbonate saturated solution is sent into the crystallization unit through a peristaltic pump, and the lithium carbonate crystal product is obtained after standing and crystallizing through multiple fibers in the crystallization component.

[0018] In step 1, specifically: 1.55 g of lithium carbonate powder is mixed with 100 ml of distilled water and stirred to obtain a saturated lithium carbonate solution;

[0019] In step 2, specifically: the freezing process uses a freezer, and freezes for 50 minutes at a temperature of -15 degrees Celsius.

[0020] In step three, the filtration process adopts normal pressure filtration method; in step four, multiple hairs or carbon fibers are tightly fixed on a glass piece so that the bottom of the fiber is immersed in the solution; the static condition is room temperature of 25 degrees Celsius.

[0021] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0022] 1. When using this component, first prepare a saturated lithium carbonate solution in a container, then place the prepared solution in a freezing component for freezing treatment to lower the solution temperature, which is conducive to subsequent crystallization, and then filter the frozen saturated solution to filter out the insoluble lithium carbonate powder, and then discharge the liquid into the crystallization component through the pump body, and crystallize by fiber. Compared with the traditional crystallization method, it can condense larger crystals, and finally discharge the waste liquid in the crystallization component through the pump body.

[0023] 2. When using this solution, multiple tree-shaped side-by-side thin glass pieces are arranged along the length direction of the crystallization frame, and fiber filaments are attached to each glass tube at the same time, so that batch crystallization can be carried out simultaneously to improve the crystallization efficiency. The tree-shaped side-by-side thin glass pieces and part of the ends of the fiber filaments are exposed to the air, and crystallization is carried out through the fibers. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic diagram of the structure of the invention as a whole;

[0025] Figure 2 is a schematic diagram of the structure of the crystallization assembly in Example 2;

[0026] Figure 3 Schematic diagram of the experimental process;

[0027] Figure 4 is the XRD analysis diagram;

[0028] Figure 5 This is a schematic diagram of another set of experiments;

[0029] Figure 6 Electron microscope images of crystals; voltage: 15kV, magnification (a) 150 / (b) 610 / (c) 300 / (d) 460 / (e);

[0030] Figure 7(Ⅰ)(Ⅱ) are electron microscope images of sample powder; (Ⅲ)(Ⅳ) are electron microscope images of cup bottom; (V)(VI)(VII) are electron microscope images of cup-shaped objects;

[0031] Figure 8 Schematic diagram of vacuum drying experiment;

[0032] Fig. 9 This is a schematic diagram of the fan acceleration experiment;

[0033] Fig.10 This is a micrograph of crystal growth;

[0034] Fig.11 Schematic diagram of other experiments;

[0035] Fig.12 The solids formed on the hair of Solution 1 and the lithium carbonate powder observed under a microscope;

[0036] Markings in the figure: 1. Freezing assembly; 2. Filtration assembly; 3. Crystallization assembly; 4. Drainage assembly; 5. Peristaltic pump; 21. Glass rod; 22. Filter paper; 23. Funnel; 31. Crystallizer; 32. Cover; 33. Glass carrier; 34. Fiber filament; 35. Crystallization frame; 36. Tree-shaped parallel thin glass parts; 321. Air vents; 351. Main frame; 352. Support tube; 353. Grip; 354. Rubber pad; 361. Main rod; 362. Support thin rod. DETAILED DESCRIPTION

[0037] All features disclosed in this specification, or steps in all methods or processes disclosed, except mutually exclusive features and / or steps, can be combined in any manner.

[0038] Any feature disclosed in this specification (including any additional claims and abstract), unless otherwise stated, may be replaced by other equivalent or alternative features having similar purposes. That is, unless otherwise stated, each feature is only an example of a series of equivalent or similar features.

[0039] In the description of the present invention, it is necessary to understand that the directions or positional relationships indicated by the terms "up", "down", "left", "right", etc. are based on the directions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a predetermined direction, be constructed and operated in a predetermined direction, and therefore cannot be understood as a limitation on the present invention.

[0040] In addition, the terms "first", "second", etc. are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first", "second", etc. may explicitly or implicitly include one or more of the features.

[0041] Example 1

[0042] like Figure 1-2 As shown, the present invention provides a technical solution:

[0043] A highly efficient and simple lithium carbonate solution crystallization component 3, which at least includes but is not limited to a freezing component 1, a filtering component 2, a crystallization component 3 and a drainage component 4; the freezing unit is used to freeze the configured solution, the filtering component 2 is used to filter the frozen solution, the crystallization component 3 is used to crystallize the filtered solution, and the drainage component 4 is used to discharge the waste liquid in the crystallization component 3; the crystallization component 3 is provided with fibers for crystallization treatment, and the filtering component 2 and the drainage component 4 are connected to the crystallization component 3 through a pump body.

[0044] Based on the above structure, when using this component, first prepare a saturated lithium carbonate solution in a container, then place the prepared solution in the freezing component 1 for freezing treatment to lower the solution temperature, which is conducive to subsequent crystallization, and then filter the frozen saturated solution to filter out the insoluble lithium carbonate powder, and then discharge the liquid into the crystallization component 3 through the pump body, and crystallize by fiber. Compared with the traditional crystallization method, larger crystals can be condensed, and finally the waste liquid in the crystallization component 3 is discharged through the pump body.

[0045] As an example, the freezing component 1 can be a freezing box, and the filtering component 2 can be a glass rod 21, filter paper 22 and a funnel 23; the filter paper 22 is placed on the funnel 23, and the lithium carbonate solution is drained onto the filter paper 22 through the glass rod 21 for filtration; the filtering component 2 and the drainage component 4 are respectively connected to the crystallization component 3 through the peristaltic pump 5.

[0046] As an example, the crystallization assembly 3 may include a crystallizer 31, a cover 32, a glass carrier 33 and fiber filaments 34; the fiber filaments 34 are arranged on the glass carrier 33, the crystallizer 31 is opened at the upper end, the cover 32 covers the crystallizer 31, and the cover 32 is provided with air holes 321;

[0047] Based on the above structure, when in use, the glass carrier 33 bonded with the fiber filaments 34 is placed in the solution of the crystallizer 31, so that at least a portion of the length of the fiber filaments 34 is in contact with the lithium carbonate solution, so that the fiber filaments 34 are rapidly crystallized.

[0048] Example 2

[0049] The present embodiment provides another form of a crystallization component 3, which may specifically include a crystallizer 31, a cover body 32, a crystallization frame 35, tree-shaped side-by-side fine glass pieces 36 and fiber filaments 34; the crystallizer 31 is opened at the upper end, the cover body 32 is provided with air holes 321, the cover body 32 covers the crystallizer 31, a plurality of tree-shaped side-by-side fine glass pieces 36 are arranged on the crystallization frame 35, and the fiber filaments 34 are arranged on the tree-shaped side-by-side fine glass pieces 36.

[0050] Based on the above structure, when in use, multiple tree-like side-by-side thin glass pieces 36 are arranged along the length direction of the crystallization frame 35, and the fiber filaments 34 are attached to each glass tube. Batch crystallization can be carried out simultaneously to improve the crystallization efficiency. The tree-like side-by-side thin glass pieces 36 and part of the ends of the fiber filaments 34 are exposed to the air, and crystallization is carried out through the fibers.

[0051] As an example, the tree-like parallel thin glass pieces 36 may include a main rod portion 361 and supporting thin rods 362, wherein the supporting thin rods 362 converge at the main rod portion 361, and the bottom of the supporting thin rods 362 forms a support, and the fiber filaments 34 are attached along the length direction of each supporting thin rod 362 and converge at the main rod portion 361.

[0052] Based on the above structure, each tree-like parallel thin glass piece 36 has a plurality of supporting thin rods 362. On the one hand, the supporting thin rods 362 can support the tree-like parallel thin glass pieces 36. On the other hand, they also provide a carrier for the fiber filaments 34 to facilitate crystallization.

[0053] As an example, the crystallization frame 35 may include a main frame 351, a support tube 352 and a gripping member 353; the support tube 352 is disposed at the top of the main frame 351, the gripping member 353 is disposed on the side wall of the support tube 352 away from the main frame 351, and a rubber pad 354 may be disposed on the inner contact portion between the gripping member 353 and the support tube 352;

[0054] The air hole 321 may be a strip hole, the length of which is not less than the length of the gripping piece 353 , so that the gripping piece 353 can pass through the air hole 321 , and the width of which is not less than the size of the supporting tube 352 .

[0055] Based on the above structure, when in use, the holding piece 353 can be rotated to a state parallel to the bar hole, pass through the bar hole, and then rotated to a state perpendicular to the bar hole, so that the holding piece 353 contacts the upper part of the cover body 32, and the main frame 351 is suspended to facilitate crystallization.

[0056] Example 3

[0057] This embodiment provides an efficient and simple method for crystallizing a lithium carbonate solution; the method specifically comprises the following steps:

[0058] Step 1: subjecting lithium carbonate powder to a solution preparation unit to obtain a saturated lithium carbonate solution;

[0059] Step 2: sending the saturated lithium carbonate solution to a freezing unit to obtain a saturated lithium carbonate solution in the form of an ice-water mixture;

[0060] Step 3: sending the saturated lithium carbonate solution in the form of an ice-water mixture into a filtration unit to remove excess undissolved lithium carbonate powder to obtain a pretreated saturated lithium carbonate solution;

[0061] Step 4: The pretreated lithium carbonate saturated solution is sent to the crystallization unit through the peristaltic pump 5, and the lithium carbonate crystal product is obtained after standing and crystallizing through the multiple fibers in the crystallization assembly 3;

[0062] In step 1, specifically: 1.55 g of lithium carbonate powder is mixed with 100 ml of distilled water and stirred to obtain a saturated lithium carbonate solution;

[0063] In step 2, specifically: the freezing process uses a freezer, and freezes for 50 minutes at a temperature of -15 degrees Celsius;

[0064] In step three, the filtration process adopts normal pressure filtration method;

[0065] In step 4, a plurality of fibers (hair, carbon fiber) are tightly fixed on a glass piece so that the bottom of the fibers are immersed in the solution; the static condition is room temperature of 25 degrees Celsius.

[0066] Example 4

[0067] This embodiment uses hair to perform crystallization:

[0068] Step 1, mixing deionized water with lithium carbonate powder, and pre-treating by stirring to obtain a preliminary mixed solution;

[0069] Step 2, sending the preliminary mixed solution into a freezer, and after freezing treatment, obtaining a completely dissolved lithium carbonate solution;

[0070] Step 3, draining the completely dissolved lithium carbonate solution through a glass rod onto a funnel with filter paper, and filtering to obtain a saturated lithium carbonate solution;

[0071] Step 4, delivering the saturated lithium carbonate solution into the crystallization device through the first peristaltic pump; attaching a sufficiently long hair to a glass sheet to form a crystallization carrier; delivering the crystallization carrier into the crystallization device, and immersing the end of the hair on the crystallization carrier into the solution of the crystallization device to obtain an assembled crystallization device; placing the crystallization device in a suitable environment, and after a period of shade drying, lithium carbonate crystals with regular shapes will be formed on the hair above the liquid surface; delivering the solution in the crystallization device after crystallization through the second peristaltic pump, taking out the crystallization carrier after crystallization, and repeating the above operation to achieve repeated crystallization.

[0072] Example 5

[0073] This embodiment uses carbon fiber for crystallization:

[0074] Step 1, mixing deionized water with lithium carbonate powder, and pre-treating by stirring to obtain a preliminary mixed solution;

[0075] Step 2, sending the preliminary mixed solution into a freezer, and after freezing treatment, obtaining a completely dissolved lithium carbonate solution;

[0076] Step 3, draining the completely dissolved lithium carbonate solution through a glass rod onto a funnel with filter paper, and filtering to obtain a saturated lithium carbonate solution;

[0077] Step 4, sending the saturated lithium carbonate solution into the crystallization device through the first peristaltic pump; bonding a carbon fiber of sufficient length to a glass sheet to form a crystallization carrier; sending the crystallization carrier into the crystallization device, and immersing the end of the carbon fiber on the crystallization carrier into the solution of the crystallization device to obtain an assembled crystallization device; placing the crystallization device in a suitable environment, and after a period of shade drying, regularly shaped lithium carbonate crystals will be formed on the carbon fiber above the liquid surface; sending the solution in the crystallization device that has completed crystallization through the second peristaltic pump, taking out the crystallization carrier that has completed crystallization, and repeating the above operation to achieve repeated crystallization.

[0078] The inventors conducted multi-angle experiments on the crystallization effect to prove that by bonding fiber filaments to glass pieces in a low-temperature saturated solution, the fiber filaments protruding from the liquid surface can be crystallized in large volume.

[0079] Experiment 1:

[0080] The laboratory uses the following devices: beaker container, stainless steel cup, plastic cup, hair, glass rod, laboratory-scale glass slide, hot melt adhesive (used to fix two glass slides), XRD instrument (used to measure XRD), carbon dioxide gas storage tank, transparent adhesive, vacuum drying oven, constant temperature oven, and the structure is as follows: Figure 3 As shown;

[0081] Take 1.55g lithium carbonate powder and dissolve it in 100ml distilled water at room temperature of 22℃, stir it thoroughly, and then put it into a thermostat and keep it in a refrigerated oven at 5℃ for 40-50min. Then take out the solution and continue to stir it evenly, then filter the solution. When the solution is filtered, stick a hair along the wall of the glass, and immerse 1 / 3 of the hair in the solution. After one day, you can see crystals precipitating around the hair. As time goes by, crystals will appear around the hair in a large area. After several months of natural evaporation, crystals will appear on the bottom of the container and the wall of the cup:

[0082] X-ray diffraction analysis (XRD, Rigaku Corporation D / max-RB) was used to characterize the crystalline morphology of the product. The diffraction peaks are diffuse and most of the energy is absorbed. The sample was tested using copper Kα radiation. The horizontal axis in the figure is twice the incident angle of the X-ray; the sample was scanned from 5° to 80° at a scanning rate of 8° / min; the results are shown in Figure 4 As shown in the figure, it can be seen that the peak values ​​all appear between θ=15° and 16.5°; the ordinate of the horizontal plane is translated upward by 8000 units, and the ordinate of the vertical plane is translated upward by 16000 units; the peak value of the vertical plane is 10000a.u.~11000a.u.; the peak values ​​of the horizontal plane and the curved surface are 7500a.u.~8000a.u.

[0083] There are two ways to put hair into a solution: one is to place it in the air without touching any surface of the container; the other is to let the hair stick to the wall of the container. Figure 5 As shown in the figure, the test results show that crystals appear on the hair attached to the container wall, while no phenomenon occurs on the hair suspended in the air. Through multiple experiments, it was observed that crystals crystallize around the hair, but they always begin to crystallize on the hair at a certain height from the liquid surface instead of directly from the liquid surface. The crystals formed by the hair appear like snowflakes, with regular shapes and large areas. Figure 6 and Figure 7 As shown, based on the electron microscope image, we can accurately measure that the diameter of the crystals produced in the laboratory is between 500μm and 1000μm; while the diameter of the sample powder is only 10μm to 15μm; it is obvious that the volume changes by 50 to 100 times from powder to crystal.

[0084] The difference between the nucleation rate and growth rate of the crystal will directly affect the final crystal morphology. If the nucleation rate of the crystal is greater than the growth rate of the crystal, more small crystals will be produced, and the crystal particles may eventually agglomerate. Conversely, larger crystals may be produced. Crystallization under vacuum conditions may accelerate the formation of a supersaturated state of the solution, thereby affecting the nucleation rate of the crystal and ultimately affecting the crystal morphology. Figure 8As shown, through a control test, a cup of prepared solution I (1.55g / 100ml) was placed in a vacuum drying oven to make it in a vacuum environment (vacuum degree is 0.07MPa); another cup of the same solution II (1.55g / 100ml) was placed outdoors; the results showed that at a temperature of 24℃~26℃ and a humidity of 45%~50%, after 24 hours, a small amount of crystals appeared on the glass plate of solution I, but the volume was very small and only a trace amount; while the solution outdoors precipitated larger crystals with more mass than a hair; another cup of the same solution III was prepared and placed in a vacuum drying oven to first evacuate the box (vacuum degree is 0.07MPa). The vacuum degree was 0.07MPa), and then CO2 gas with a temperature of 25°C and a pressure of 0.07MPa was introduced to make the air pressure inside and outside the vacuum drying oven the same; after 24 hours, the vacuum degree rose from 0MPa to 0.01MPa; however, no crystals were precipitated on the glass plate of solution III; after standing for one month, the liquid levels of solution I and solution III did not drop, and there was white strip-shaped lithium carbonate at the bottom of solution I, while solution III was colorless and accompanied by a pungent odor; the two cups of solution were taken out and placed outdoors, and crystals were precipitated in the two cups of solution after one day of standing; the crystals of solution I were smaller, and the crystals of solution III were larger.

[0085] like Fig. 9 As shown, the sample is placed in a constant temperature box, and then the temperature is changed by changing the ambient temperature of the beaker; then a fan is placed opposite the beaker, and the speed is changed by changing the wind speed of the fan; we compare two samples (one of which is placed in a room with a slow air flow rate and a high temperature, and the other is placed in a constant temperature box with a fast air flow rate and a low temperature). After 24 hours, the sample with a slow air flow rate and a high temperature grows more crystals, but the volume is small; the sample with a fast air flow rate and a low temperature grows fewer crystals, and the volume is larger;

[0086] like Fig.10 The following is the crystal appearance under a microscope (the left side is low speed and high temperature, the right side is high speed and low temperature):

[0087] This program also does Fig.11 The experiment shown in the figure shows that large-area crystals can be formed on both flat and curved surfaces, and the shape is regular and snowflake-like. The experiment shows that whether on the vertical or horizontal surface, the crystals will grow around the hair. Therefore, the crystal surface has almost no effect on the crystallization of lithium carbonate;

[0088] In this study, we found that whether lithium carbonate can crystallize is mainly affected by the carrier, temperature and container; the crystallization effect of glass container is the best. The second is plastic cup, while stainless steel cup cannot form crystals on the surface with hair; when the temperature is low, the crystals grow slowly but the particles are larger, and then there is the influence of the growth surface; the crystals grown on the curved surface have a larger spreading surface, and the crystals grown on the vertical plane have a smaller spreading surface. The crystal growth is concentrated, and the growth on the horizontal surface is the most difficult, so the amount of growth each time is small. (The volume comparison between the three can be found through electron microscopy) At the same time, experimental verification shows that in a pure carbon dioxide gas environment, the solubility of lithium carbonate powder is greater than at room temperature; in a pure carbon dioxide environment, 1.55g of powder is completely dissolved in 100ml of distilled water (it cannot be completely dissolved at normal room temperature, and even a lot of powder will remain at the bottom of the container), and the solution is clear without any impurities, and the solution has a pungent smell; although there is no crystallization phenomenon in a pure carbon dioxide gas environment, the volume of the crystals obtained by taking the sample out and placing it outdoors is significantly larger than the volume of the crystals directly placed outdoors; at the same time, the experiment also found that after vacuum standing, the crystals formed by taking out and placing outdoors The volume of the crystals produced is much smaller than the volume of the carbon dioxide environment and the volume of crystallization at normal room temperature; if carbon dioxide gas is directly introduced, the dissolution of the solid will be accelerated; when too much solid powder is added and then placed outdoors, crystals will appear on the liquid surface and inside the liquid, not just on the wall and hair; then if a hair is placed without contact with the container wall, the hair will not play a role in crystallization, and only when it is close to the wall or in contact with the wall will the hair play a role in crystallization; the diameter of the original sample powder is about 10μm~15μm and the diameter of the generated crystal is about 500μm~1000μm; it can be seen that the change in volume is quite obvious.

[0089] Lithium carbonate crystallization experiment:

[0090] 1. Equipment: iron stand, refrigerator (-9 degrees Celsius), electronic balance, lithium carbonate powder, beaker, glass rod, filter paper, and hair.

[0091] 2. Steps:

[0092] 1. Use an electronic balance to weigh 1.55g of lithium carbonate powder;

[0093] 2. Pour 100 ml of distilled water into a beaker to prepare a 0.0155 g / ml lithium carbonate solution;

[0094] 3. Prepare 3 cups of the same lithium carbonate solution and name them solution 1, 2, and 3 respectively;

[0095] 4. Put solution 1 directly into the refrigerator and freeze it for 5 hours, then take it out and observe whether it is frozen. Then put it at natural room temperature and slowly warm it up.

[0096] Solutions 2 and 3 were placed in the same conditions and frozen for 42 minutes before being taken out;

[0097] After taking out solutions 2 and 3, place solution 2 directly at room temperature of 25 degrees Celsius to air dry naturally;

[0098] After taking out solution 3, filter the solution, put it into the refrigerator again for 1.5 hours, take it out, and let it dry naturally at room temperature;

[0099] 5. Put a hair in each of the three cups of solution, with the hair sticking to the wall of the cup. Leave them together for two days and observe the phenomenon.

[0100] 3. Observation phenomenon:

[0101] 1. Observe solution 1. After freezing for five hours, it was found that solution 1 had frozen. After standing for two days, it melted. The solvent was reduced, and a white solid precipitated at the bottom of the cup with a dense shape.

[0102] 2. Observe solution 2. After standing, it is found that the solvent has decreased, and white solids are precipitated on the wall and bottom of the cup. The surface of the white solid at the bottom of the cup is smooth, and the solid forms a ring on the wall of the cup in the shape of a small snowflake (after shaking the solution, the ring falls off and sinks to the bottom of the cup). A long section of white solid is found on the hair. After taking it out along the hair with the hand and gently crushing it with the hand, the long section of solid breaks into two sections;

[0103] 3. Observe solution 3. When it was taken out of the refrigerator, it was found that it had formed an ice-water mixture. After standing, it was found that the solvent had decreased and no solid was precipitated, but white snowflake-like solids appeared on the hair.

[0104] 4. Place the three solutions together at room temperature for several days and observe again. Solution 1 has large pieces of discolored snowflake-like solids, and the snowflake-like solids in solutions 2 and 3 have become significantly larger. Solution 1 has large pieces of discolored snowflake-like solids.

[0105] IV. Control Experiment

[0106] 1. Steps:

[0107] Prepare two identical 0.0155 g / ml lithium carbonate solutions, freeze filter, and freeze for 35 min. In one solution, place the hair vertically in the center of the beaker, which is called solution 5. In the other solution, place two strands of hair against the wall of the beaker, which is called solution 4.

[0108] Prepare 300 ml of a lithium carbonate solution with a concentration of 0.0155 g / ml, recorded as solution 6. After freeze filtration, put solution 5 back into the refrigerator for 1.5 hours. After taking it out, let it dry naturally at room temperature and observe the phenomenon.

[0109] Prepare two 300ml cups of 0.0155g / ml lithium carbonate solution, named solution 7 and 8, take them out after freeze filtration, put a hair close to the wall of the cup, leave it to dry naturally at room temperature, and observe the phenomenon;

[0110] Prepare two 100 ml cups of 0.0155 g / ml lithium carbonate solution, freeze filter and place a hair close to the wall of each cup, place one cup at room temperature to air dry naturally, record as solution 10, place one cup in a vacuum dryer, evacuate the device, and let it air dry naturally, record as solution 9;

[0111] Then, a certain amount of carbon dioxide is passed through the vacuum dryer where the solution 9 is located, and a cup of distilled water is placed in the device, and the solution is allowed to air dry naturally. After standing for two days, the distilled water is taken out and allowed to air dry naturally.

[0112] Prepare two 100ml cups of solution containing 4.65g of lithium carbonate, put a hair in each cup and stick it to the wall of the cup. One cup is left to air dry at room temperature, which is called solution 12; the other cup is left to air dry under vacuum, which is called solution 13.

[0113] Prepare 100 ml of 0.0155 g / ml lithium carbonate solution, referred to as solution 11. After freeze filtration, continue to power solution 11 at 12 V for 10 min, then put a hair close to the wall of the cup and let it air dry naturally at room temperature.

[0114] Solution 8 was continuously energized at 12V, and then allowed to air dry naturally at room temperature;

[0115] 67g of the solution containing impurities was frozen and then continuously energized at 6V2A, and then allowed to air dry naturally at room temperature, and hair that had already formed white snowflake-like solids was placed in the solution;

[0116] The solution with impurities was continuously energized at 0.3V, and then left to air dry at room temperature. A hair with white solids was placed in the solution, and the phenomenon was observed after one day. A sufficient amount of carbon dioxide was then introduced into the solution, and the phenomenon was observed after one day.

[0117] Heat the solution with impurities with an alcohol lamp, and observe the phenomenon after leaving it for one day;

[0118] 2. Observation phenomenon:

[0119] Both solutions did not reach the state of an ice-water mixture. No solid precipitated from solution 4, but white snowflake-like solids appeared on the two hairs of solution 5. Compared with the solids obtained from solution 3, it was found that the snowflakes of solution 5 were smaller and no solid precipitated from the bottom of the cup.

[0120] After leaving solution 4 at room temperature for several days (9.28 / 10.6), it was found that the solids on the two hairs became significantly larger; the solvent of solutions 5 and 6 was reduced, and long white solids appeared on the hairs, and the size was almost the same.

[0121] Solutions 7 and 8 had less solvent, and white snowflake-like solids appeared on the hair, which were almost the same size;

[0122] After 7 days of standing, white snowflake solids appeared on the hair and the wall of the cup in solution 10, and the solvent was reduced, while there was no obvious phenomenon in solution 9. After the second standing, it was found that solution 9 still had no obvious change;

[0123] After standing for three days, the phenomenon was observed and it was found that the solvents in the two cups of solution had hardly changed, and white long truncated solids appeared on the hair;

[0124] After standing for one day, solution 11 was observed and it was found that the solvent was significantly reduced, and a large amount of white fan-shaped solids and a small amount of snowflake-shaped white solids appeared on the hair. The speed at which the solids appeared was significantly faster than that of the solution without electricity.

[0125] After standing, observe solution 8 and find that the solvent is significantly reduced, a ring-shaped white solid appears on the wall of the cup, and white snowflake-like solids appear on the hair on the original basis. The speed of solid appearance is significantly faster than that of the solution without electricity.

[0126] When electricity was passed through the solution containing impurities, white granular solids were precipitated on the anode, and turned green after leaving the solution. After air-drying at room temperature, the solution and the precipitated granular solids turned reddish brown. A large amount of reddish brown solids and black solids were precipitated in the solution, and the snowflake-like solids on the hair did not change significantly.

[0127] After two standings, there was no obvious phenomenon of impurity solution;

[0128] 5. Microscope observation

[0129] 1. Observe the solids formed on the hair from Solution 1 and the lithium carbonate powder under a microscope (the microscope magnification is 100 times), and it is found that the size of the solids is obviously larger than that of the lithium carbonate powder. Fig.12 shown.

[0130] Air velocity comparison experiment:

[0131] Temperature: 23-27; Standing time: 48 hours;

[0132] After 1.55 g / 100 ml of solution 1 was left standing in an environment with a vacuum degree of 0.03 (0.07 for complete vacuum) for 48 hours, the vacuum degree dropped by 0.06, no crystals appeared on the hair fibers, and the solid at the bottom of the container showed a wavy void shape.

[0133] After 1.55 g / 100 ml of solution 1 was left standing in an open environment for 48 hours, obvious white crystals appeared on the hair fibers, and there was no obvious change in the solid at the bottom of the container.

[0134] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An efficient and simple lithium carbonate solution crystallization assembly, characterized in that: At least including but not limited to a freezing component, a filtering component, a crystallization component and a drainage component; the freezing unit is used to freeze the prepared solution, the filtering component is used to filter the frozen solution, the crystallization component is used to crystallize the filtered solution, and the drainage component is used to drain the waste liquid in the crystallization component; The crystallization component is provided with fibers for crystallization treatment, and the filtering component and the drainage component are connected to the crystallization component through a pump body.

2. An efficient and simple lithium carbonate solution crystallization assembly as claimed in claim 1, characterized in that: The freezing component is a freezing box, and the filtering component is a glass rod, filter paper and a funnel; the filter paper is placed on the funnel, and the lithium carbonate solution is drained onto the filter paper through the glass rod for filtering; the filtering component and the drainage component are respectively connected to the crystallization component through a peristaltic pump.

3. An efficient and simple lithium carbonate solution crystallization assembly as claimed in claim 1 or 2, characterized in that: The crystallization assembly comprises a crystallizer, a cover, a glass carrier and fiber filaments; the fiber filaments are arranged on the glass carrier, the upper end of the crystallizer is opened, the cover is covered on the crystallizer, and the cover is provided with air holes.

4. An efficient and simple lithium carbonate solution crystallization assembly as claimed in claim 1 or 2, characterized in that: The crystallization assembly includes a crystallizer, a cover, a crystallization frame, tree-shaped side-by-side thin glass pieces and fiber filaments; the upper end of the crystallizer is opened, the cover is provided with air holes, the cover is covered on the crystallizer, a plurality of tree-shaped side-by-side thin glass pieces are arranged on the crystallization frame, and the fiber filaments are arranged on the tree-shaped side-by-side thin glass pieces.

5. An efficient and simple lithium carbonate solution crystallization assembly as claimed in claim 4, characterized in that: The tree-like parallel thin glass pieces include a main rod portion and supporting thin rods, the supporting thin rods converge at the main rod portion, the bottoms of the supporting thin rods form supports, and the fiber filaments fit along the length direction of each supporting thin rod and converge at the main rod portion.

6. An efficient and simple lithium carbonate solution crystallization assembly as claimed in claim 5, characterized in that: The crystallization frame includes a main frame, a support tube and a holding piece; the support tube is arranged at the top position of the main frame, the holding piece is arranged on the side wall of the support tube away from the main frame, and a rubber pad is arranged on the inner contact part of the holding piece and the support tube.

7. An efficient and simple lithium carbonate solution crystallization assembly as claimed in claim 6, characterized in that: The air vent is a strip-shaped hole, the length of which is not less than the length of the gripping piece, so that the gripping piece can pass through the air vent, and the width of which is not less than the size of the supporting tube.

8. An efficient and simple method for crystallizing a lithium carbonate solution; characterized in that: The specific steps include: Step 1: subjecting lithium carbonate powder to a solution preparation unit to obtain a saturated lithium carbonate solution; Step 2: sending the saturated lithium carbonate solution to a freezing unit to obtain a saturated lithium carbonate solution in the form of an ice-water mixture; Step 3: sending the saturated lithium carbonate solution in the form of an ice-water mixture into a filtration unit to remove excess undissolved lithium carbonate powder to obtain a pretreated saturated lithium carbonate solution; Step 4: The pretreated lithium carbonate saturated solution is sent into the crystallization unit through a peristaltic pump, and the lithium carbonate crystal product is obtained after standing and crystallizing through multiple fibers in the crystallization component.

9. An efficient and simple lithium carbonate solution crystallization method as claimed in claim 8, characterized in that: In step 1, specifically: 1.55 g of lithium carbonate powder is mixed with 100 ml of distilled water and stirred to obtain a saturated lithium carbonate solution; In step 2, specifically: the freezing process uses a freezer, and freezes for 50 minutes at a temperature of -15 degrees Celsius.

10. An efficient and simple lithium carbonate solution crystallization method as claimed in claim 8, characterized in that: In step 3, the filtration process adopts the normal pressure filtration method; in step 4, a plurality of hairs or carbon fibers are tightly fixed on the glass piece so that the bottom of the fiber is immersed in the solution; The static condition is room temperature of 25 degrees Celsius.

Citation Information

Patent Citations

  • Method and system for rapid extraction of lithium carbonate from salt lake water

    CN103318928A

  • Crystallization tower for gas phase reaction

    CN106345135A

  • Method for recycling lithium from battery-grade lithium carbonate mother liquid

    CN110451536A

  • Self-supporting lithium metal negative electrode material and preparation method and application thereof

    CN112054203A

  • Lithium extraction solar pond

    CN215855144U

Cited By

  • Lithium ion extraction device based on secondary crystallization method

    CN116715308A

  • A lithium ion extraction device based on a secondary crystallization method

    CN116715308B